(untitled) (TAMADDUN NURI JURNALI, 2025)
This article presents a poetic analysis of the ghazal “Aylansun” by Shermuhammad Munis. Through the depiction of the beloved’s beauty and presence, the poet conveys themes of spiritual love, devotion, repentance, and supplication using Sufi symbols. The ghazal features rich use of metaphors, similes, paronomasia, and symbolic imagery that reflect the lyrical subject’s inner mystical state. Munis’s poetic style shows strong influence of Persian-Tajik ghazal traditions blended with a distinctly Uzbek lyrical tone.